(untitled) (Tempo e Argumento, 2011)
This paper seeks to identify the movements of joints and preservation of cultural identity on the island of Santa Catarina, which occurs implicitly in the revitalization of events such as Carnival Zé Pereira, who for more than one hundred years occurs in the vicinity of Ribeirão da Ilha district, in Florianópolis / SC, which in recent years has been highlighted in planning the carnival events in Santa Catarina, both in the media, as the increase in the number of participants. The choice of musical repertoire, from the leaders of the Musical Society and Recreation Lapa, which promotes the event, and the manifestations of the communities involved and the media in relation to the rhythms performed, generate discussions that can enrich the very issues that involve the preservation cultural events involving the town, listed by the local historical heritage.